A method of source localization for bioelectricity based on "Orthogonal Differential Potential". (September 2021) - Shang, Shuaijie; Li, Gang; Lin, Ling
Highlights: Propose a new method for dipole source localization. "Orthogonal Differential Potential" can extract the azimuth of the single dipole model. The new method can more accurately locate the dipole depth. Abstract: Objective: The present aim is to investigate "Orthogonal Differential Potential" to take further steps in developing dipole source localization (DSL) technology, which can help us to better explain the position and state of the signal source in an organism. Methods: In this paper, we examined the feasibility of the new method by evaluating the performance of an inverse algorithm we developed to localize a single dipole model from the surface potential. In computer simulations, the Laplacian was calculated according to the ordinary potential on the gird. Then we defined the information in the orthogonal direction of the Laplacian as "Orthogonal Differential Potential." Through "Orthogonal Differential Potential, " we extracted the azimuth of the single dipole model and located dipole depth. In the physical experiments, the new method and the conventional method were both used to process the experimental data of the same parameters. Results: The result showed that: Compared with the conventional method, the new method can quickly detect the dipole azimuth and more accurately locate the dipole depth. And when the depth of dipole is in the range of 1–5 cm, the maximum relative error of the new method can be controlled within ± 0.3%. Conclusion: Our study shows that "Orthogonal Differential Potential" is an effective method for extracting the azimuth of the single dipole model and locating dipole depth. Significance: The new method is expected to be more widely used in disease diagnosis and basic clinical research in the future.